Pemanfaatan Kulit Pisang Menjadi Selai Dalam Program Zero Waste Di Desa Godog Kabupaten Sukoharjo - Khoirunnisa, Aisyah Hanum; Devina Artarani, Sheva; Putri Anjani, Dewi; Sholikhah Akhiroh, Ninuk (Jurnal Bina Desa, 2024)
Banana peels which have long been considered waste possess significant nutritional potential and can be innovatively utilized. In Godog Village, Sukoharjo, processing banana peels into jam offers a solution to enhance the added value of local products and support the Zero Waste program. A training session on making banana peel jam held in the village successfully raised community awareness about the benefits of banana peels and reduced organic waste. This activity involved the PKK mothers and the community, starting with a socialization of the Zero Waste concept, followed by a jam-making demonstration. The results of the training showed participants' enthusiasm and a new understanding of the potential for consuming banana peels. Thus, this activity not only provides a healthy food alternative but also supports the local economy and promotes a more environmentally friendly lifestyle.